Experimental study on cobalt adsorption by bone powder modified with poly Pyrrole and polyethylene glycol - Javad Yarmohammadi Jamaloi; Majid Riahi Samani; Davood Toghraie (Results in Engineering)
Heavy metals, including cobalt, are significant pollutants in water and wastewater. This study investigates the use of bone powder and a bone powder/poly-pyrrole composite for the removal of cobalt from aqueous solutions through batch experiments. The results indicate that the highest cobalt removal percentage achieved was 68.06 %, while the lowest was 59.80 %. These variations were attributed to the addition of polyethylene glycol and polyvinyl alcohol at concentrations of 3 g/L and 1 g/L, respectively, during the synthesis of the bone powder/poly-pyrrole composite. The influence of solvent type on the removal efficiency revealed that the highest removal percentage (57.07 %) was attained using butanol and water solvents in the presence of 3 g/L PEG. Increasing the initial pH of the solution enhanced the adsorption capacity, with maximum cobalt adsorption observed at pH 7. The optimal composite adsorbent demonstrated an equilibrium time of 30 mins. Additionally, the pseudo-second-order kinetic model was identified as the best fit for cobalt adsorption, based on the correlation coefficient (R²). The removal efficiency increased to 92.18 % when the adsorbent dose was raised from 2 g/L to 8 g/L, with a corresponding increase in cobalt removal. The experimental data conformed to the Langmuir isotherm model, as indicated by the adsorption isotherm results.